SISTEM INFORMASI MODEL SUPERVISI KLINIK BERBASIS MANAJEMEN PENGETAHUAN DALAM MENINGKATKAN MUTU PEMBELAJARAN - Indadihayati, Warda (Jurnal Dinamika Manajemen Pendidikan, 2020)
This study aims to develop a supervisi klinik model based on proses manajemen pengetahuan in improving the quality of learning. The research design uses research and development (R & D) with the stages of data collection, product planning and design, initial product development, product validation, revision of validation results, field trials, and revisions and final product improvements. Information system development outcomes at the stage (1) identification of potential teacher condition as supervisor; (2) implementation of supervision activities through pre-observation, observation and post-observation stages with clinical instruments that can be stored online; (3) the best practice of learning that can be accessed to share instructional innovations; (4) the existence of an online teacher performance appraisal archive